Forecasting Model of Coffee Berry Borer (Hypothenemus Hampei) in Pasuruan District - Nadiah, Annisrien; Himawan, Toto; Tarno, Hagus (Research Journal of Life Science, 2023)
Coffee, a globally important commodity, faces difficulties in Indonesia due to pests that reduce its quality and productivity. The coffee berry borer (Hypothenemus hampei) is particularly dangerous, causing hollowed-out coffee seeds and causing massive annual losses worldwide and in Indonesia. Factors such as climate, weather, and other environmental aspects play a pivotal role in influencing pest lifecycles, emphasizing the necessity of understanding the intricate relationship between pests and their environment for effective management. This research aims to contribute to minimizing coffee production losses and harvest failures resulting from H. hampei infestations. This study relies on secondary data from the BBPPTP in Surabaya and NASA. Using panel data regression analysis, the study discovers that coffee berry borer attacks in the Pasuruan District follow a seasonal pattern. Furthermore, with a forecasting accuracy of 15.94%, the model reveals that air humidity, temperature, and previous attacks are the dominant variables influencing current coffee berry borer attacks. The developed model provides a reliable tool for forecasting coffee berry borer attacks, with humidity and previous month's attacks emerging as the most influential factors, particularly in the Pasuruan District of East Java.